A comparative study of FESEM and EDX analyses of Datong coal in N2 and CO2 environments. (February 2016) - Irfan, Muhammad Faisal
Abstract: Field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy and Brunauer Emmett Teller surface area analyses of char produced in CO2 and N2 environments in a thermo-gravimetric analyzer, using thermo-plus II software, were investigated under different parametric conditions. These conditions include temperature, flow rate variations etc. for the implementation of oxy-fuel combustion technology. It was observed that, at high temperatures and low flow rates, the mass loss rate of coal in CO2 was higher than in that of a N2 environment. This may be due to one additional step of coal gasification i.e. char gasification by CO2 at higher temperature. More importantly, during the reaction with CO2 the formations of perfectly hexagonal nanorods at the particular temperature of 773 K were observed. However, the amount of these nanorods decreases and the dimensions i.e. size and shape change (smaller aspect ratio) with the increase of flow rate and temperature as well. The formation of these nanorods are attracted much because of their peculiar properties and potential applications in functional nano-devices and environmentally clean energy purposes i.e. CO2 capturing. Highlights: Compared the coal-char produced in N2 and CO2 environments for the oxyfuel combustion. Formation of nanorods in CO2 environment were observed. The produced chars were analyzed by BET, FESEM and EDX techniques. Both cheap coal and CO2 were used as raw materials for production of nanorods using TGA.